The environmental experience during daylight and dark conditions: a conceptual model for pedestrians and cyclists / La experiencia ambiental en condiciones de luz diurna y oscuridad: Un modelo conceptual para peatones y ciclistas - Rahm, Johan; Niska, Anna; Johansson, Maria (Psyecology, 2024)
Walking and cycling are considered sustainable transport modes, promoted as a means to reduce car traffic. In the scientific literature, they have mostly been investigated separately, but should be considered jointly to enable a modal shift. Both daytime and dark conditions need to be studied, to improve understanding of how environmental features are affected by temporal variation. A conceptual model is introduced to advance understanding of the significance of different environmental factors for walking/cycling, and serves as the basis for the design of an empirical study. A between-subject design was used, comparing two pedestrian/cycle paths located in two mid-sized Swedish cities during daytime and after dark. Pedestrians (n = 90) and cyclists (n = 74) responded to questionnaires assessing environmental parameters hypothesized to be of importance for walking and cycling. Three-factor ANOVAs indicated differences between the two locations (perceived stimuli), between pedestrians and cyclists (environmental appraisal, affective response, behavioural intention) and between daytime and dark conditions (visual accessibility, restorative potential). The conceptual model helps identify the importance of various environmental features.